The Dashboard: an online system to help build an online presence and measure analytics for micro-businesses - Davies, Mark; Greenhalgh, Chris; Glover, Kevin; Chamberlain, Alan; Crabtree, Andy; Valchovska, Stela; Rodden, Tom (2013)
Digital marketing plays an important role for businesses trying to attract new customers. For micro-businesses (0-9 workers) or self- run businesses it can be difficult to find the time to market yourself online. Non tech-savvy individuals can be unaware of where to start or how to set up a website. It can be time consuming, costly and difficult to understand the digital requirements. In this paper, we describe an online system - the dashboard, to help micro-businesses learn about building an online presence, using a range of available digital services, and providing analytical data on services that they are using. We discuss how analytic tools can help inform business owners of how useful online marketing tools are for their business and which services attract the most customers and revenue.